Evaluation of the results of the prevention program "Protect your voice" implemented by The Greater Poland Center of Occupational Medicine of Poznań - Magdalena Jałowska; Grażyna Wośkowiak; Bożena Wiskirska-Woźnica (Nofer Institute of Occupational Medicine, 2017)
Background: The aim of the study was to evaluate the rationale for training in voice emission and voice prophylaxis among teachers and to assess the effects of voice disorders rehabilitation in the selected group of teachers participating in the program "Protect your voice." Material and Methods: An anonymous survey was conducted among 463 teachers participating in the training part of the program. The effectivness of rehabilitation of teachers with occupational voice disorders was evaluated among 51 subjects (average age: 43 years) taking part in diagnostic and rehabilitation part of the program. Phonation voice exercises with speech therapist and physiotherapy (iontophoresis, inhalations and elektrostimulation) were administered. Evaluation of rehabilitation was based on phoniatric examination, including videostroboscopy and statistical calculations. Results: The survey showed that among teachers there is high demand (98%) for training in proper voice emission, hygiene and prevention of voice. The effectiveness of rehabilitation has been confirmed by the observed improvements in phonatory activities of larynx, proper breathing during phonation (p = 0.0000), the voice quality (p = 0.0022), prolonged phonation time (an average of 1.39 s), increased number of people who correctly activated resonators (p = 0.0000) and increased number of people with phonation without excesive muscle tension of the neck. Conclusions: The results indicate that among all the professionally active teachers, there is a need for regular training of proper voice emission and vocal hygiene and then conduct individually phonation and breathing exercises, supported by the physiotherapy. This should be an effective method of voice disorders prevention in teachers. Med Pr 2017;68(5):593-603